The Implementation of Waste Management Policy in Creating a Clean, Comfortable and Healty Environment at the City of Jambi Jambi Province - Arsento, Mezi; Hamdi, Muchlis; Ngadisah, Ngadisah; Simangunsong, Fernandes (Budapest International Research and Critics University, 2022)
The problem of waste management in Jambi City is still not effective and less than optimal, it can be seen that there are still many obstacles and expectations that have not been achieved from the implementation of the waste management policy. The increase in the amount of waste is in line with the increasing population growth in the Jambi City area, while the landfill area is getting narrower. Waste management carried out by the Jambi City Government from upstream to downstream which applies the 3R concept (Reuse, Reduce, and Recycle) does not run optimally due to the lack of facilities and infrastructure, so that the amount of waste generated in the landfill is increasing every year. The quality of education for apparatus resources in the relevant agencies is still low. This study uses a qualitative method with construction characteristics that are built based on natural conditions, are more descriptive, emphasizes more on the process, the analysis is done inductively, and places more emphasis on the value or meaning contained in a data or event. The results of research and discussion on the implementation of waste management policies in Jambi City, Jambi Province, from the legal basis are clearly linear from the national level to the Jambi City level, but in practice the implementation has not involved elements of the community even though Jambi City has received an award in early 2021, Jambi City in regional ranks who excel at the national level and succeeded in bringing Jambi City into the 13 regions in Indonesia that won awards in the field of waste management, the success of a policy if community elements can feel the results of the policy, in this context the researcher concludes that the policy is good but in the future it will be better Community elements must be involved as beneficiaries of waste management policies in Jambi City, Jambi Province. Researchers found a new model of this research, namely a collaborative model for handling waste, elements of the government, private sector, community, business world in waste management policies in Jambi City, Jambi Province, as a solution to solving problems in handling solid waste in Jambi City.